Modus Tokoro Da Dalam Film Animasi Jepang - Citra Dewi; Nunik Nur Rahmi Fauzah; Nadya Ayasmin (Diponegoro University, 2022)
This study discusses the formation of the structure of the modus tokoro da based on Kato's (1989) theory. The purpose of this study is to describe the structure of the modus tokoro da. In the process of collecting data, the author uses the listening method with a note-taking technique based on Mahsun's (2013) theory. In analyzing the structure of the modus tokoro da, the author uses the agih method with the direct element division (BUL) technique based on Sudaryanto's theory (2015). In writing this research, the author uses a qualitative descriptive method based on the theory of Sugiyono (2019). The data used is sourced from the fermi lab (ferumi kenkyuujo) youtube channel and supernatural genre anime. In this study, the data containing the tokoro da mode amounted to 45 data, but the data displayed in this study amounted to 15 data. The result of this research is that the modus structure of tokoro da is formed from the verb ru+tokoro da, the verb teiru+tokoro da, the verb ta+tokoro da, and the verb teita+tokoro da. Each verb attached to the modus tokoro da has a different type of verb, namely the modus tokoro da attached to the type of verb keizoku doushi totaling 7 data, the modus tokoro da attached to the type of verb shunkan doushi totaling 6 data, and the modus tokoro da being attached to the type the joutai doushi verb has 2 data. From this research, it can be concluded that the modus tokoro da is more dominantly attached to the type of verb keizoku doushi than the type of verb shunkan doushi and joutai doushi. Compared to previous studies which only stated that the structure of tokoro da was formed from tokoro da which was attached by verb ru, verb te iru, and verb ta. In this study, there is novelty where the verbs attached to the modus tokoro da have different types, namely joutai doushi, keizoku doushi, shunkan doushi, and daiyonshu no doushi (Kindaichi, 1989, pp. 9–11). The discussion in this study is useful for readers to understand the structure formed from the modus tokoro da by adding an explanation of the types of verbs attached to the modus tokoro da.